2001
DOI: 10.1002/joc.693
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic climate variability: phenomena, impacts and mechanisms

Abstract: Variability of the North Atlantic Oscillation and the Tropical Atlantic dominate the climate of the North Atlantic sector, the underlying ocean and surrounding continents on interannual to decadal time scales. Here we review these phenomena, their climatic impacts and our present state of understanding of their underlying cause. Copyright

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
741
0
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 909 publications
(802 citation statements)
references
References 270 publications
(261 reference statements)
45
741
0
16
Order By: Relevance
“…Nevertheless, other atmospheric circulation patterns can be identified during the boreal winter in Western Europe (Barnston and Livezey, 1987). These patterns have an important role in the climatology of the western Mediterranean area (Marshall et al, 2001;Rodríguez-Puebla et al, 1998;Krichak and Alpert, 2005;Dünkeloh and Jacobeit, 2003).…”
Section: General Atmospheric Circulation Patternsmentioning
confidence: 99%
“…Nevertheless, other atmospheric circulation patterns can be identified during the boreal winter in Western Europe (Barnston and Livezey, 1987). These patterns have an important role in the climatology of the western Mediterranean area (Marshall et al, 2001;Rodríguez-Puebla et al, 1998;Krichak and Alpert, 2005;Dünkeloh and Jacobeit, 2003).…”
Section: General Atmospheric Circulation Patternsmentioning
confidence: 99%
“…The most important phenomena on interannual to decadal timescale in this region are the Pacific El Niño-Southern Oscillation (ENSO), the Atlantic zonal equatorial mode (or the 'tropical Atlantic Niño') and the tropical Atlantic meridional gradient (TAMG) (or the 'tropical Atlantic dipole index') (Berlage, 1957;Giannini et al, 2000;Marshall et al, 2001;Martis et al, 2002;Rajagopolan et al, 1997;Robertson and Mechoso, 2002;Villwock, 1998;Wang, 2001Wang, , 2005. The above phenomena are caused by the variability in sea-surface temperatures (SSTs).…”
Section: Introductionmentioning
confidence: 99%
“…The different mechanisms are schematically shown in Figure 1. Garzoli et al (1999); Giannini et al (2000); Marshall et al (2001) and Villwock (1998) have shown that the rainfall in northern South America is more related to the sea-surface temperature anomalies (SSTAs) in the tropical North Atlantic (TNA) than to the tropical South Atlantic (TSA) and the tropical Pacific ENSO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These extend throughout the troposphere but peak around The NAO is expressed in tropical Atlantic SSTs and air pressure (Venzke et al, 1999;Marshall et al, 2001), and relationships with southern Angola river flows can be tested. The Kavango time series exhibits spectral energy at both interannual and decadal periods, consistent with SST fluctuations in the tropical North Atlantic (Melice and Servain, 2003;Andreoli and Kayano, 2004).…”
Section: Synthesis Of Seasonal Patterns and Their Statisticsmentioning
confidence: 99%